"The Ties That Bind": Springsteen Fans Reflect on the Live Concert Experience. Issue 1 (2nd January 2016) - Baxter-Moore, Nick
Abstract : As the traditional driving forces of the music business, sales of recorded music and music publishing, have experienced serious economic downturns over the last decade, principally as a result of changes in technology and consumer behavior, one of the few growth areas in the broader music industry has been the live performance and touring sector. Yet, there are remarkably few academic studies of this sector: for example, we know very little about why people attend live concerts, how they evaluate the concerts they have attended, and why they keep going back, often to see the same artist they have already seen, sometimes many times on the same tour. This paper analyzes on-line postings by Bruce Springsteen fans and concertgoers in order to develop a framework to conceptualize the live concert experience and fans' motivations for returning to attend multiple concerts, often on the same tour.